Observations on stratified flow over a bank at low Froude numbers. Issue 9 (22nd September 2014) - Jarosz, Ewa; Wijesekera, Hemantha W.; Teague, William J.; Fribance, Diane B.; Moline, Mark A.
Abstract In June 2011, a 9 day oceanographic survey was conducted over the East Flower Garden Bank, a coral reef, located on the outer shelf in the northwestern Gulf of Mexico. Current, temperature, conductivity, and microstructure measurements were collected to characterize flow evolution, turbulence, and mixing over the bank. During the experiment, the flow was highly stratified, subcritical (Froude number below 0.4), hydrostatic, and nonlinear with rotational effects being important. Observations showed that flow structure, turbulence, and mixing were highly dependent on the direction and strength of the current; thus, they varied spatially and temporarily. Responses resulting from interactions between the free‐stream flow and the obstacle were significantly different on the upstream and downstream sides of the bank. Blocking and diverging of the flow just below the bank height was observed on the upstream side. On the downstream side, a wake with imbedded vortices developed. Moreover, turbulence was amplified over the bank top and on its downstream side. Turbulent dissipation rates were as high as 10−6 W kg−1 and resulted in measured rates of energy dissipation and mixing by turbulence per unit width as high as 40 W m−1. Mixing on the downstream side was elevated with eddy diffusivities reaching 10−3 m2 s−1, well above a typical value of 10−5 m2 s−1 commonly found in the ocean thermocline and over shelves with flat topography. On the upstream side, estimated eddy diffusivities were close to that for the ocean thermocline, i.e., they were generally less than 0.5×10−4 m2 s−1.